ARCHITECTING COMPOSABLE SECURITY. Issue 2 (July 2016) - Dōne, Brian K.; Willett, Keith D.; Benjamin, Bruce P.; Sterne, Dan F.; Tally, Gregg W.; Viel, David W.
ABSTRACT: Cyber adversaries' reuse similar tools and techniques. Cyberspace‐attack response times are currently too slow because existing response solutions require humans in the loop. Many cyber alerts are never analyzed due to lack of available analyst time, which enable attacks to gain a deeper penetration before detection and remediation. Today's existing cyber defense approaches cannot be scaled due to the labor‐intensive nature. Integrated Adaptive Cyberspace Defense (IACD) seeks to improve cyber security automation, increase information sharing, and encourage interoperability between commercial tools to achieve composable security where the right tools are engaged at the right time for the right reasons.